2014
DOI: 10.3402/gha.v7.25598
|View full text |Cite
|
Sign up to set email alerts
|

Disease-specific mortality burdens in a rural Gambian population using verbal autopsy, 1998–2007

Abstract: ObjectiveTo estimate and evaluate the cause-of-death structure and disease-specific mortality rates in a rural area of The Gambia as determined using the InterVA-4 model.DesignDeaths and person-years of observation were determined by age group for the population of the Farafenni Health and Demographic Surveillance area from January 1998 to December 2007. Causes of death were determined by verbal autopsy (VA) using the InterVA-4 model and ICD-10 disease classification. Assigned causes of death were classified i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…For any such event, these are then validated with the village reporter. However it is still possible that the number of deaths, and more specifically neonatal deaths[ 25 ], may have been underestimated, possibly resulting in an underestimation of the association.…”
Section: Discussionmentioning
confidence: 99%
“…For any such event, these are then validated with the village reporter. However it is still possible that the number of deaths, and more specifically neonatal deaths[ 25 ], may have been underestimated, possibly resulting in an underestimation of the association.…”
Section: Discussionmentioning
confidence: 99%
“…Over the 7-year period, the study observed significant number of deaths and cause-specific mortality. Overall, mortality rates in the area were lower compared to those previously reported in other parts of Tanzania [37, 38] and sub-Saharan Africa [3942]. The main reasons for declining trends in mortality, apart from the decline in malaria burden, could include socio-economic development, improved health services, such as the establishment of primary health care, provision of preventive services and immunization.…”
Section: Discussionmentioning
confidence: 64%
“…Almost half of the population is under the age of 15 years, and in 2016 life expectancy was estimated at 61 and 63 years for males and females, respectively [12]. The only available data on CVD in the Gambia, derived from a health and demographic surveillance system, show that stroke went from being the third most frequent cause of death among the 60+ age group in 1998-2001 to the top cause of death in 2005-2007 [13].…”
Section: Introductionmentioning
confidence: 99%